Characterization of 15 CYP2J2 variants identified in the Chinese Han population on the metabolism of ebastine and terfenadine in vitro - Zou, Li-Li; Zhao, Fang-Ling; Qi, Yu-Ying; Wang, Shuang-Hu; Zhou, Quan; Geng, Pei-Wu; Zhou, Yun-Fang; Zhang, Qing; Chen, Hao; Dai, Da-Peng; Cai, Jian-Ping; Ji, Fu-Sui (Frontiers in Pharmacology, 2023)
Genetic polymorphism of the cytochrome P450 (CYP) gene can significantly influence the metabolism of endogenous and xenobiotic compounds. However, few studies have focused on the polymorphism of CYP2J2 and its impact on drug catalytic activity, especially in the Chinese Han population. In this study, we sequenced the promoter and exon regions of CYP2J2 in 1,163 unrelated healthy Chinese Han individuals using the multiplex PCR amplicon sequencing method. Then, the catalytic activities of the detected CYP2J2 variants were evaluated after recombinant expression in S. cerevisiae microsomes. As a result, CYP2J2*7, CYP2J2*8, 13 variations in the promoter region and 15 CYP2J2 nonsynonymous variants were detected, of which V15A, G24R, V68A, L166F and A391T were novel missense variations. Immunoblotting results showed that 11 of 15 CYP2J2 variants exhibited lower protein expression than wild-type CYP2J2.1. In vitro functional analysis results revealed that the amino acid changes of 14 variants could significantly influence the drug metabolic activity of CYP2J2 toward ebastine or terfenadine. Specifically, 4 variants with relatively higher allele frequencies, CYP2J2.8, 173_173del, K267fs and R446W, exhibited extremely low protein expression and defective catalytic activities for both substrates. Our results indicated that a high genetic polymorphism of CYP2J2 could be detected in the Chinese Han population, and most genetic variations in CYP2J2 could influence the expression and catalytic activity of CYP2J2. Our data significantly enrich the knowledge of genetic polymorphisms in CYP2J2 and provide new theoretical information for corresponding individualized medication in Chinese and other Asian populations.